Nicholaus de Heybech of Erfurt, Table Maker and Copyist - Chabás, José; Goldstein, Bernard R. (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2023)
Nicholaus de Heybech (fl. 1384–1394) is the author of a clever and compact solution to a major challenge for medieval astronomers: finding the time from mean to true syzygy. His table and associated canon for that purpose are now found in 30 manuscript copies, which means that this table was one of the most widely diffused single tables in Alfonsine astronomy. In this article, we present two different and hitherto unnoticed tables by Nicholaus de Heybech for determining mean syzygy, which nicely complement the table that is already known, and we gather the information available on another aspect of his activity beyond table making, as a copyist of texts and tables mainly in mathematical astronomy.